Spectrum Degradation of Hippocampal LFP During Euthanasia - Zhou, Yuchen; Sheremet, Alex; Kennedy, Jack P.; DiCola, Nicholas M.; Maciel, Carolina B.; Burke, Sara N.; Maurer, Andrew P. (Frontiers in Systems Neuroscience, 2021)
Abstract. The hippocampal local field potential (LFP) exhibits a strong correlation with behavior. During rest, the theta rhythm is not prominent, but during active behavior, there are strong rhythms in the theta, theta harmonics, and gamma ranges. With increasing running velocity, theta, theta harmonics and gamma increase in power and in cross-frequency coupling, suggesting that neural entrainment is a direct consequence of the total excitatory input. While it is common to study the parametric range between the LFP and its complementing power spectra between deep rest and epochs of high running velocity, it is also possible to explore how the spectra degrades as the energy is completely quenched from the system. Specifically, it is unknown whether the 1/f slope is preserved as synaptic activity becomes diminished, as low frequencies are generated by large pools of neurons while higher frequencies comprise the activity of more local neuronal populations. To test this hypothesis, we examined rat LFPs recorded from the hippocampus and entorhinal cortex during barbiturate overdose euthanasia. Within the hippocampus, the initial stage entailed a quasi-stationary stage when the LFP spectrum exhibited power-law feature while the frequency components over 20 Hz exhibited a power decay with a similar decay rate. This stage was followed by a rapid collapse of power spectrum towards the absolute electrothermal noise background. As the collapse of activity occurred later in hippocampus compared with medial entorhinal cortex or visual cortex, it suggests that the ability of a neural network to maintain the 1/f slope with decreasing energy is a function of general connectivity. Broadly, these data support the energy cascade theory where there is a cascade of energy from large cortical populations into smaller loops, such as those that supports the higher frequency gamma rhythm. As energy is pulled from the system, neural entrainment at gamma frequency (and higher) decline first. The larger loops, comprising a larger population, are fault-tolerant to a point capable of maintaining their activity before a final collapse.